(untitled) (gjstudies, 2021)
The escalating global environmental crisis has precipitated an unprecedented demand for corporate accountability regarding environmental impact. Environmental auditing has emergedas a critical mechanism for verifying corporate environmental claims and ensuring the integrity of sustainability reporting. However, traditional environmental auditing approacheshave predominantly focused on regulatory compliance and procedural verification, oftenfailing to assess the substantive quality and verifiability of environmental disclosures. Thisresearch addresses this significant gap by developing and validating a novel multidimensionalenvironmental auditing framework that integrates computational methodologies to evaluateboth the form and substance of corporate environmental accountability